MANAJEMEN STRATEGI MENGGUNAKAN PORTER’S FIVE FORCES UNTUK MENINGKATKAN EFISIENSI APLIKASI PINJAMAN MELALUI OTOMATISASI DAN SOSIALISASI INKLUSIF DALAM PROGRAM PERUMAHAN MELALUI DINAS TNI AL - Saputra, Brian Winata Adi; Faeni, Dewi Puspaningtyas (SINERGI : Jurnal Riset Ilmiah, 2025)
The Indonesian Navy Private Housing Program (PPMD TNI AL) is a major initiative to improve the welfare of Indonesian Navy personnel by facilitating access to homeownership through structured housing finance loans. However, the program faces significant challenges, such as inefficiencies in the loan application process, outdated administrative procedures, and inadequate outreach to potential beneficiaries. This study uses Porter's Five Forces framework to critically analyze inefficiencies in the current loan application process. This analysis provides insights into the barriers that impact the program's effectiveness. Furthermore, the study proposes the integration of automation technology to streamline the application and verification process, reduce manual errors, and improve overall efficiency. An inclusive outreach strategy is also recommended to ensure equitable access to the program, meeting the needs of all eligible personnel. By combining these approaches, the program can improve its operational efficiency, expand accessibility, and build a more sustainable system to support private homeownership among Indonesian Navy personnel. This strategy aims to align the program's objectives with the welfare priorities of its beneficiaries, ensuring broader outreach and greater impact